2022
DOI: 10.1093/gji/ggac192
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing tectonic subsidence in the Lesser Antilles subduction zone

Abstract: Summary Geological estimates of vertical motions in the central part of the Lesser Antilles show subsidence on timescales ranging from 125.000 to 100 years, which has been interpreted to be caused by interseismic locking along the subduction megathrust. However, horizontal GNSS velocities show that the Lesser Antilles subduction interface is currently building up little to no elastic strain. Here we present new present-day vertical velocities for the Lesser Antilles islands and explore the link … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Microatolls studies along the eastern coasts of the island (Hog Hole) revealed that this island subsided as a response of interseismic strain accumulation over more than five decades at rate of about 5mm/yr. The sign of those vertical deformations is compatible, with that of the vertical 575 deformation estimated with a GNSS station located few kilometers away to the west, but larger by an order of size (0.5 mm/year +/-1 for a time period between 1994, van Rijsingen et al, 2022. In this area, Weil-Accardo et al (2022) studied a set of quaternary reef terraces and showed that the eastern part of Barbuda has undergone a long-term uplift of 0,05 to 0.1 mm/year over the last 330 Ka.…”
supporting
confidence: 80%
“…Microatolls studies along the eastern coasts of the island (Hog Hole) revealed that this island subsided as a response of interseismic strain accumulation over more than five decades at rate of about 5mm/yr. The sign of those vertical deformations is compatible, with that of the vertical 575 deformation estimated with a GNSS station located few kilometers away to the west, but larger by an order of size (0.5 mm/year +/-1 for a time period between 1994, van Rijsingen et al, 2022. In this area, Weil-Accardo et al (2022) studied a set of quaternary reef terraces and showed that the eastern part of Barbuda has undergone a long-term uplift of 0,05 to 0.1 mm/year over the last 330 Ka.…”
supporting
confidence: 80%
“…However, investigations on some coral micro-atolls suggest that vertical deformation are possibly related to a local increase in interseismic coupling at great depth (Philibosian et al, 2022). A more recent study (van Rijsingen et al, 2022) has however, presented vertical velocities for the Lesser Antilles Islands and examine the link between the short and long-term vertical motions and their underlying processes. Based on their elastic dislocation models, they show that a locked or partially locked interplate up to 60 km depth would produce uplift of the island arcs, which is opposite to the observations of microatolls and GNSS data.…”
Section: Seismicity and Seismogenic Zonementioning
confidence: 99%
“…Far to the southeast, along the Lesser Antilles Subduction Zone, an 1843 earthquake of estimated magnitude M7.8–M8.5 produced hardly any tsunami (Bernard & Lambert, 1988). The megathrust earthquake potential in this area was recently debated (Philibosian et al., 2022; van Rijsingen et al., 2022).…”
Section: Introductionmentioning
confidence: 99%